Expanding Access to Early Childhood Development : Using Interactive Audio Instruction - World Bank Group; Education Development Center (World Bank Group, Washington, DC, 2015)
The returns to investments in early childhood development (ECD) are manifold and can include improved school readiness, reduced drop-out rates, higher labor force productivity and greater social cohesion. Despite these high returns, enrollment in early childhood education is just 18 percent across Africa, with disproportionately high enrollment from children in urban areas and from wealthier families. Interactive Audio Instruction (IAI) is a distance learning technology that can deliver low-cost, culturally appropriate education via radio or mobile audio technology. It is a highly effective tool to reach children who can be hard to reach through conventional programs, including the rural poor and children with disabilities. IAI can also be an effective form of service delivery in unstable and conflict-affected regions.